Acrylamide Analog as a Novel Nitric Oxide-Independent Soluble Guanylyl Cyclase Activator - Masaki Nakane; Teodozyi Kolasa; Renjie Chang; Loan N. Miller; Robert B. Moreland; Jorge D. Brioni (Elsevier, 2006)
Soluble guanylyl cyclase (sGC) is a target enzyme for endogenous nitric oxide (NO), and it converts GTP to cyclic GMP (guanosine 3',5'-cyclic monophosphate) as part of a cascade that results in physiological processes such as smooth muscle relaxation, neurotransmission, and inhibition of platelet aggregation. Here we examine a representative of the novel class sCG activators, A-778935 ((±)-cis-3-[2-(2,2-dimethyl-propylsulfanyl)-pyridin-3-yl]-N-(3-hydroxycyclohexyl)-acrylamide). A-778935 activated sGC synergistically with sodium nitroprusside (SNP) over a wide range of concentration, inducing up to 420-fold activation. A specific inhibitor of sGC, ODQ (1H-[1,2,4]-oxadiazolo[4,3-α]quinoxalin-1-one), did not block basal sGC activity, but competitively inhibited the activation by A-778935. A-778935, with or without SNP, did not activate heme-deficient sGC, indicating that the activation of sGC by A-778935 is fully heme-dependent. A-778935 increased intracellular cGMP level dose-dependently in smooth muscle cells. In the presence of 1 µM SNP, a lower concentration of A-778935 increased cGMP than A-778935 alone, and the cGMP concentration reached the same level at 100 µM of A-778935. A-778935 relaxed cavernosum tissue strips in a dose-dependent manner; and in the presence of 1 µM SNP, A-778935 relaxed the strips more potently, shifting the dose-response curve to the left. This novel activator of sGC may have potential efficacy for the treatment of a variety of disorders associated with reduced NO signaling. Keywords:: soluble guanylyl cyclase, activator, nitric oxide, YC-1, sodium nitroprusside